Drawing at the Nanoscale through Macroscopic Movement. Issue 6 (27th April 2022) - Xu, Chao; Liu, Hong; Yang, Shikuan
Abstract: Nanopatterns are important for applications in various nanodevice fields. Existing nanopatterning techniques mainly directly manufacture the nanopatterns through various lithographic methods, which usually are laborious, time‐consuming, and need expensive equipment. Here, an extremely simple drawing at the nanoscale (DAN) concept to indirectly fabricate rational nanopatterns through controlling the macroscopic movement of the substrate, is demonstrated. The structure of the nanopatterns is completely determined by and can be shrunk by millions of times from the moving track of the substrate. Multiple surface nanopatterns of different materials with accurately tailorable relative positions can be simply stacked together by moving the substrate by macroscopic distances during different DAN processes. In combination with sophisticated lithographic methods, the DAN method is anticipated to enable substantial advances in nanofabrication. Abstract : A technique capable of drawing at the nanoscale is introduced through controlling the macroscopic movement of the substrate. The structure of the surface nanopatterns is completely determined by the macroscopic moving track of the substrate and the size shrinking time from the macroscopic movement track to surface nanopatterns can be accurately manipulated and easily reach million times.